ACC740: Quantitative and Qualitative Data Analysis / Faculty of Accountancy - UiTM, Faculty of Accountancy (Universiti Teknologi MARA (UiTM), 2018)
This course focuses on the statistical analysis of business related and social sciences problems, and the use of medium to advanced statistical methods as tools for answering research enquiries. This encompasses the understanding and application of appropriate statistical analysis techniques, the use of powerful statistical software for data analysis, statistical reporting and presentation. The qualitative research is intended to provide the student with the basic skills needed to do qualitative research that focuses on understanding, rather than prediction or controlling, phenomena. It usually contrasted with traditional experimental and statistical research and is felt by many to be more appropriate to the study of human life. Included will be discussion of and practice in basic phenomenological description, structural analysis, research interviewing, and the repertory grid.